Pengaruh penggunaan model pembelajaran guided inquiry terhadap minat belajar siswa kelas VIII SMP Negeri 1 Toari - Rahayu, Deti Sri (Karoteh Utama, 2023)
This research aims to investigate the impact of implementing the Guided Inquiry learning model on the level of students' interest in learning in the eighth grade of SMP Negeri 1 Toari. This study uses a quantitative method with a quasi-experimental approach. Two classes were selected as the experimental and control groups, with sample selection using a random sampling technique. Data were collected through questionnaires distributed to students. Data analysis was conducted to test the proposed hypotheses. Before hypothesis testing was performed, prerequisite tests, such as the normality test, were conducted to ensure that the data were normally distributed. The test results indicated that the data met the normality assumption. Homogeneity testing was also conducted, and the results showed that both groups had homogeneous variances. Subsequently, a paired sample t-test was conducted to examine the significance of the impact of the Guided Inquiry learning model on the interest in learning of eighth-grade students at SMP Negeri 1 Toari. The results of the analysis showed a significant impact of implementing the Guided Inquiry learning model on students' interest in learning.